To Justifying of the Humanistic Theory of Complexity of Society - S. A. Kravchenko (Vestnik MGIMO-Universiteta, 2013)
In article problems of the introduction of mankind in the difficult society which intrinsic line is the formation which is occurring not linearly, with accompanying risks, traumas, gaps, paradoxes are considered. The author claims that adequate interpretation of these processes does necessary humanistic turn in sociology. Respectively, the interdisciplinary humanistic theory of complexity which itself is at a formation stage, is capable to prove approaches to implementation of humanistically focused modernization of the Russian society.